Second Report to the Niue Assembly on the Constitutional Development of Niue - Quentin-Baxter, R Q (Victoria University of Wellington Law Review, 1999)
Professor Quentin-Baxter provides suggestions to the Niue Island Assembly regarding the directions of Niue’s constitutional development. The first part of the report provides the background to this report, including the need for Niue to have its own constitution while maintaining Niue’s free association with New Zealand. The second part of the report discusses the contents of the proposed constitution, including requirements for public consultation, guarantees of New Zealand citizenship and economic and administrative assistance, the constitution’s role as a public safeguard of certain legislative areas, and the future role of the Niue Island Assembly. The final part of the report is an addendum which includes a speech from Professor Quentin-Baxter regarding additional topics that the author did not include in the main body of the report, including calling for the establishment of a Niue Public Service Commission.